"Stubborn things: evidence, postmodernism and the craft of history.". Issue 1 (14th November 2018) - Muldoon, Jeff
Abstract : Purpose: The purpose of this paper is to review the recent book A New History of Management (NHM) and to discuss the strengths and limitations of the book versus traditional management history as practiced by Wren and Bedeian. Design/methodology/approach: I analyze NHM by looking at the evidence presented in the book versus the historical record. Findings: Although there are some strengths to NHM, the scholars often fail to address the larger historical evidence, which reduces the value of their work. Originality/value: The value is to start a discussion of the nature of management history by discussing traditional versus postmodern history. Hopefully, the authors can commence with a dialogue to further historical research.